Phonological units for phonological change: synchrony shall provide them - Zelenskii, Dmitrii (Papers in Historical Phonology, 2021)
The question of what types of units and domains are needed in order to capture phonological change is a reasonable one to ask. To answer this question, however, we first need to properly define how we understand phonological change, and the definition that we adopt for that clearly depends on the phonological framework that is assumed. I consider several influential frameworks here and then come to the conclusion that the same condition holds for all of them: change can only be described in terms of the same units (and domains) as are used for synchronic description. This leads to the following conclusion: the set of units for phonological change is a subset of the set of units that are needed for synchronic phonological description. However, it is also unlikely that some units needed for synchronic description can be fully ignored for all descriptions of changes, which leads us to the conclusion that the set of units that are needed for phonological change is also a superset of that set. The sets are thus equal: the phonological units needed for synchronic description are the units needed to account for phonological change, and the question above is meaningless.